2012
DOI: 10.1007/s10562-012-0831-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal Support Interactions in Co3O4/Al2O3 Catalysts Prepared from w/o Microemulsions

Abstract: To obtain nano-sized metal and metal salt crystallites with a narrow size distribution synthesis methods utilizing water in oil (w/o) microemulsions, i.e. reverse micelles, have been widely applied and reported in literature. In this study we show the effect of support addition at different stages of the reverse micelle based preparation of cobalt oxide on alumina model catalysts. All catalysts were characterized with X-ray powder diffraction and Raman spectroscopy indicating the presence of Co 3 O 4 on the Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…The energy separation between the Co 2p 3/2 and Co 2p 1/2 peaks is $15 eV, in good agreement with a standard Co 3 O 4 sample [10]. The Co 2p 3/2 core levels are mainly observed at $779.9 eV and $780.7 eV, corresponding to the binding energies of Co 3 O 4 and Co(OH) 2 phases [11,12]. In particular, metal-OH species inhibit CO poisoning on the catalyst's surface by oxidizing adsorbed CO to CO 2 [13,14].…”
Section: Resultssupporting
confidence: 81%
“…The energy separation between the Co 2p 3/2 and Co 2p 1/2 peaks is $15 eV, in good agreement with a standard Co 3 O 4 sample [10]. The Co 2p 3/2 core levels are mainly observed at $779.9 eV and $780.7 eV, corresponding to the binding energies of Co 3 O 4 and Co(OH) 2 phases [11,12]. In particular, metal-OH species inhibit CO poisoning on the catalyst's surface by oxidizing adsorbed CO to CO 2 [13,14].…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, in a Co‐son/γ‐Al 2 O 3 spectrum (Figure a), a shoulder around 500 cm −1 is formed that is not observed for the reference material. The research groups of Fischer et al and Kock et al correlate this band position with the creation of a CoAl 2 O 4 structure on the surface . It can therefore be concluded that the cobalt atoms could also be adsorbed on the alumina surface and be incorporated into its lattice upon thermal treatment.…”
Section: Resultsmentioning
confidence: 95%
“…[65] Generally, paramagnetic Co 2 + exhibits more intense satellite peaks than Co 3 + . [66] However, Co 2p spectra of samples synthesized in the presence or absence of H 2 O 2 do not display pronounced differences (see Figure S12, Supporting Information). By contrast, Co 3p spectra of Co 3 O 4 _20 h_H 2 O 2 exhibit a significant broadening and peak shift toward higher bonding energy as compared to Co 3 O 4 _20 h. Two peaks around 62.5 eV and 59.5 eV in the fitted Co 3p spectra can be assigned to Co 3 + and Co 2 + , respectively, and the results clearly demonstrate that the presence of H 2 O 2 during hydrothermal synthesis led to a higher Co 3 + /Co 2 + ratio in Co 3 O 4 _20 h_H 2 O 2 particles ( Figure 10).…”
Section: Resultsmentioning
confidence: 99%